Pharmacokinetics of PEGylated Recombinant Human Erythropoietin in Rats - Xiaohan Cao; Zhiyong Chen; Zhuoran Yu; Yonghong Ge; Xianyin Zeng (Journal of Analytical Methods in Chemistry)
rHuEPO plays a central role as chemicals for the treatment of many diseases. Due to its short half-life, the main aim for this pharmacokinetic study is to investigate a newly developed PEG-rHuEPO with large molecular weight in SD rats. After a single intramuscular administration of different doses of 125I-PEG-rHuEPO, pharmacokinetic parameters, tissue distribution, and excretion were analyzed. In in vivo half-life time measured after 125I-PEG-rHuEPO administration at the doses of 1, 2, and 3 μg/kg, t1/2α was 1.90, 1.19, and 2.50 hours, respectively, whereas t1/2β was 22.37, 26.21, and 20.92 hours, respectively; at 8, 24, and 48 hours after intramuscular administration, PEG-rHuEPO was distributed to all of the examined tissues, however, with high concentrations of radioactivity, only in plasma, blood, muscle at the administration site, and bone marrow. Following a 2 μg/kg single intramuscular administration, approximately 21% of the radiolabeled dose was recovered after almost seven days of study. Urine was the major route of excretion; 20% of the administered dose was recovered in the urine, while excretion in the feces was less than 1.4%. Therefore, this PEG-rHuEPO has potential to be clinically used and could reduce frequency of injection.